2014
DOI: 10.1111/cid.12239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nicotine in the Corrosive Behavior of a Ti‐6Al‐4V Dental Implant

Abstract: At certain concentrations, nicotine inhibits local corrosion; however, it also prevents the formation of a protective oxide film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This is why, the implementation of more clinical and laboratory studies for the detection of any adverse effects of titanium's particles on the body's cells is highly suggested. [17] Royhman et al [18] evaluated the corrosion effect of nicotine on Ti-6Al-4V under physiological conditions. It was hypothesized that nicotine in artificial saliva would have an adverse side effect on the corrosion of Ti-6Al-4V.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why, the implementation of more clinical and laboratory studies for the detection of any adverse effects of titanium's particles on the body's cells is highly suggested. [17] Royhman et al [18] evaluated the corrosion effect of nicotine on Ti-6Al-4V under physiological conditions. It was hypothesized that nicotine in artificial saliva would have an adverse side effect on the corrosion of Ti-6Al-4V.…”
Section: Resultsmentioning
confidence: 99%
“…This research may assist in formulating strategies to improve dental implant success and survival rates in patients, who consume nicotine products routinely. [18] Flatebo et al [19] demonstrated the presence of corrosion titanium particles in the tissue adjacent to Ti cover screws. However, Ti particles may be released during insertion of the fixture and may be retained in the covering soft tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was proven that infection, the presence of nicotine and soft drinks with varying pH levels might impose challenges on the implant surfaces by shifting the normal potential to very anodic values. 25,42,43 It can be noted that 1-CaP10 and 1-CaPAg10 had their potentiodynamic curves shifted to the upper-left region of the graph, demonstrating nobler potential and lower current compared to other groups.…”
Section: B Tribocorrosion Testsmentioning
confidence: 93%
“…Findings revealed that the corrosion rate of titanium decreased with a increase in nicotine concentration. However, the presence of nicotine also negatively affected the passive film formation, being that the passive current density and polarization resistance were reduced, leading to the worst overall surface performance [63].…”
Section: Corrosion Processes and Measurement On Titanium Surfacesmentioning
confidence: 99%